Seismic response of a five story building with isolation system and supplemental viscous dampers for peruvian seismicity - Taboada Saavedra, Diego Enrique (2019)
Projects with seismic isolation are increasing in Peru, even the Peruvian Seismic Standard establishes that seismic isolators must be used in hospitals located in seismic zones 4 and 3 of the Peruvian seismic map. It is also accepted that there may be isolated buildings on floors S0, S1, S2 and S3. In isolated buildings that are in soil type S3 and seismic zone 4, maximum displacement values ​​are obtained. This involves the use of flexible connections, plus in some cases these offsets result in a smaller usable area of ​​the building. An alternative to reduce these displacements is the use of supplemental viscous dampers at the base of the isolated building, which adds damping to the isolation system. In this investigation, a mathematical model of a 5-story building with elastomeric isolators, located in seismic zone 4 and soil type S3, was evaluated. This model was then analyzed with supplemental viscous dampers, considering 5 different damping percentage conditions: 15%, 30%, 45%, 60% and 75%. For all analyses, 7 time history records compatible with Peruvian seismicity were used. Isolated base displacement reductions will be acquired up to 30% of their starting value. The variation of the responses (accelerations, deviations, shear forces and dissipated energy) was analyzed as a function of the increase in damping. It was verified that the Peruvian seismic combination of isolators and dampers tends to increase the responses of the superstructure.